Reforming and remembering: gardens and gardening in a landscape of in/justice. (3rd April 2021) - Hutchison, Mary
ABSTRACT: This paper charts the changing cultural-personal uses and meanings of Port Arthur gardens from penal settlement, to rural township, to heritage site as a way of reflecting on the process of reforming and remembering the site as a material and discursive landscape of in/justice. It draws on contemporary and first-person accounts of the ideology and experience of Port Arthur gardens and uses both expository and descriptive forms of writing to show the gardens as agents of brutality and inequity, as resistance and healing.